A dilemma for women: having many children risks deterioration of diastolic functions - Mehmet Ozgeyik; Ozge Turgay Yildirim; Mevlut Serdar Kuyumcu; Mehmet Ali Astarcioglu (IMR Press, 2021)
Background: Echocardiography is the most widely used diagnostic tool for detecting changes in cardiac function. Pregnancy is a dynamic process that affects the cardiovascular system and recent studies have shown that increased parity may cause irreversible changes in the cardiovascular system. In this study, we aimed to evaluate echocardiographic changes in women, especially grand multiparous (6 to 9 parities) and great grand multiparous (more than 9 parities) women, after all their pregnancies had finished. Methods: This was a cross-sectional study and contained 195 female patients. Women with one delivery were defined as primiparous (PP), 2 to 5 deliveries were defined as multiparous (MP), 6 to 9 deliveries were defined as grand multiparous (GMP) and more than 9 deliveries were defined as great grand multiparous (GGMP). Results: The mean age at cardiac evaluation was 50.6 ± 16.3 and mean parity was 6.5 ± 4.2. Diastolic dysfunction was grouped as grade 1-3 and this was determined according to the E/e' ratio. Spearman correlation analysis showed that diastolic dysfunction had positive correlations with parity, age, hypertension, and diabetes mellitus. Receiver-operating curve (ROC) analysis showed that the best cut-off value of the parity number for predicting left ventricular diastolic dysfunction was 6.5, with 66.3% sensitivity and 66.7% specificity. Discussion: In the present study, we showed that diastolic dysfunction significantly increased as the number of pregnancies increased. Additionally, the cut-off value of parity for diastolic dysfunction was 6.5 which is higher than other studies.